The Redefinition of Foreign Policy of the United States since Trump’s Election: The Case of Trade War with China - Jaskuła, Paweł (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
The main aim of this text is to present economic relations between China and the US today. The election of Donald Trump in 2016, significantly redefined American trade policy toward China. Despite the first months of his presidency, which promised an efficient, long-term cooperation between Beijing and Washington, incumbent president decided to implement severe restriction on the trade with China at the beginning of 2018. However, the announced imposition of tariffs on almost all goods coming from this country could interfere with the growth of the single states and the economy of the whole country in the future. Therefore the text is aimed to investigate the ependency of selected states on the inflows of Chinese investments since 2010. Finally, it is necessary to examine the phenomenon of the trade war, which has begun in July 2018, and assess its impact on the growth of both countries.